Prevalence, risk factors, and management practices of premenstrual syndrome among female university students in Lebanon: An observational cross-sectional study - Rania Itani; Reem Al Rawass; Diala Tlayss; Fatima Al Zarif; Souraya Domiati; Chaza Alaeddine; Mohamad Abdallah; Rawad Hayouk (PLoS ONE, 2026)
Background Premenstrual syndrome (PMS) is common among women of reproductive age and may impair quality of life, academic performance, and social functioning. In Lebanon, data on PMS and its management among female university students remain limited. This study aimed to estimate the prevalence of PMS among female university students in Lebanon, identify risk factors, and recognize adopted management practices and their perceived effectiveness. Methods An observational cross-sectional study was conducted among female students at Beirut Arab University, Lebanon, between April 20 and May 8, 2026. Data were collected using a self-administered questionnaire assessing sociodemographic, menstrual, lifestyle, behavioral, psychosocial, and management-related factors. Premenstrual symptoms, social media addiction, and perceived stress were assessed using the Premenstrual Symptoms Screening Tool, Bergen Social Media Addiction Scale, and Perceived Stress Scale-4, respectively. Binary logistic regression was used to identify factors associated with moderate-to-severe PMS and premenstrual dysphoric disorder (PMDD). Results Among 1,062 participants, 497 participants screened positive for moderate-to-severe PMS (46.8%), and 175 had symptoms consistent with PMDD based on the PSST (16.5%). The most frequently reported moderate-to-severe symptoms were physical symptoms (69.7%), fatigue or lack of energy (68.8%), depressed mood or hopelessness (67.8%), and overeating or food cravings (66.2%). Academic absenteeism was reported by 37.2%. More than one-third of the participants with moderate-to-severe PMS and PMDD (39%) reported using pharmacological management practices, mainly non-steroidal anti-inflammatory drugs. However, less than half of medication users perceived these treatments as being very effective (45.8%). Higher odds of moderate-to-severe PMS were observed among current smokers (AOR = 1.61, P = 0.003), those with heavy menstrual bleeding (AOR = 1.58, P = 0.03), high meal skipping (AOR = 1.38, P = 0.03), high fast-food consumption (AOR = 1.34, P = 0.04), higher social media addiction scores (AOR = 1.31, P < 0.001), and higher perceived stress scores (AOR = 1.48, P < 0.001). Conclusion PMS was common among female university students in Lebanon and a considerable proportion experienced PMDD. In fact, lifestyle, behavioral, and psychosocial factors were associated with moderate-to-severe symptoms, highlighting the need for university-based awareness, screening, and counseling strategies that address modifiable risk factors and support appropriate management of premenstrual symptoms.